Association Between Regulatory Emotional Self-Efficacy and Immunosuppressive Medication Adherence in Renal Transplant Recipients:Does Medication Belief Act as a Mediator? - Liu, Jia; Zhu, Xiao; Yan, Jin; Gong, Lina; Wu, Xiaoxia; Liu, Min; Mao, Ping (Frontiers in Pharmacology, 2021)
Background:Few studies have investigated the association between regulatory emotional self-efficacy (RESE) and immunosuppressive medication(IM) adherence or the mechanisms underlying this relationship. Considering that previous evidence of IM adherence depended on the level of IM beliefs, a model of multiple mediation was tested in which IM beliefs acted as mediators of the relationship between RESE and IM adherence. Methods:A retrospective cross-sectional study was performed in 293 renal transplant patients during outpatient follow-ups from November 2019 to February 2020 in China. All participants completed a general demographic questionnaire, the Chinese version of the RESE, the Beliefs about Medication Questionnaire, and the Basel Assessment of Adherence with IM Scale (BAASIS). Spearson correlation analysis was carried out to identify the correlation between RESE and IM adherence. Binary logistic regression analysis was performed to confirm factors associated with IM adherence in renal transplant recipients. Mediating effect analysis was used to explore the internal interaction between RESE and IM adherence. Results:A total of 293 renal transplant patients were recruited, including 111 women and 182 men with a mean age of 42.5 years (SD = 10.0). A total of 23.21% of patients exhibited IM none-adherence behavior, and 12.97% reported altering the prescribed amount of IM without physician permission, which was most popular behavior among patients. The mean RESE score was 45.78±6.12; the positive (POS) score was the highest, and the anger-irritation (ANG) score was the lowest. The correlation analysis results showed that RESE (r=-0.642, p < 0.01) and IM beliefs (r=-0.534, p<0.01) were significantly associated with IM adherence.Binary logistic regression analysis indicated that marital status, fertility status,rejection, IM beliefs, and RESE were found to be independent predictors of IM adherence [R2=0.803, p<0.05]. The results of the mediating effect analysis showed that IM necessity had a partial mediating effect, RESE directly and indirectly affected IM adherence via IM necessity, and IM concerns were not a mediator between RESE and IM adherence. Conclusion: IM adherence in renal transplant patients need to be improved in China. Marital status, fertility status, rejection, IM beliefs, and RESE were major factors affecting IM adherence. RESE could affect IM adherence indirectly through IM necessity.